(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2023)
Accounting is one of the basic functions of manage- ment directed at providing economic security and elimi- nates the possibility of direct theft without occurrence by law consequences, provides information conditions for the control expediency and legal utilization resources, facili- tate implementation prevent threats which reduces eco- nomic enterprise stability. Reporting unit’s role in the en- terprise is determined depending on the level at which the accounting data are used and appropriate solutions. if the financial accounting department and play an essential role in deciding that their influence on the final result is much higher. Leading role in the system of economic security be- longs accounting department.